Limiting the Use of AI By Creating Regulations that Can Prevent the Occurring of Digital Crime - Husana, Salma Maulida; Hibatullah, Farid; Romdoni, Muhamad (LAW FACULTY UNISSULA, 2024)
Artificial Intelligence (AI) has acquired an increasingly important role in various aspects of human life, including in the digital domain. However, the rapid development of AI technology also carries significant risks, especially related to the potential for misuse to commit digital crimes. Therefore, this research aims to propose effective regulations to limit the use of AI to prevent digital crimes. In the midst of the rapid development of AI technology, the risk of misuse for online crimes is increasing. Regulations must include transparency in the use of AI, data protection, and effective monitoring and enforcement. Collaboration between agencies and stakeholders will be key in designing and implementing these regulations, ensuring that AI is used for the common good and security. This review identified several forms of digital criminal activity that could be enabled by the use of AI, including cyberattacks, online fraud and the spread of illegal content. Factors influencing the increased risk of digital crime using AI are also explored, including technological sophistication, lack of security awareness, and the power imbalance between regulators and criminals. By considering these various factors, this study aims to evaluate the effectiveness of regulations in controlling the use of artificial intelligence (AI) to prevent digital crime. Combining analysis of the latest digital crime trends and expert insights, this research identifies potential threats, analyzes the layers of protection required, and suggests regulations that can be implemented. The results of this research are in the form of regulatory recommendations that can be implemented to control the use of artificial intelligence (AI) to prevent digital crime. The recommendations include certification requirements for AI developers, restrictions on the types of data that can be used by AI, and strict enforcement against violations.